2018
DOI: 10.1242/jcs.223792
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of destruction – in vitro reconstitution methods in autophagy research

Abstract: Autophagy is one of the most elaborative membrane remodeling systems in eukaryotic cells. Its major function is to recycle cytoplasmic material by delivering it to lysosomes for degradation. To achieve this, a membrane cisterna is formed that gradually captures cargo such as organelles or protein aggregates. The diversity of cargo requires autophagy to be highly versatile to adapt the shape of the phagophore to its substrate. Upon closure of the phagophore, a doublemembrane-surrounded autophagosome is formed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 176 publications
0
5
0
Order By: Relevance
“…[ 51 ] Moreover, the trapping and transport of organelles on the particle provide a new ex vivo platform for organelle manipulation and analysis, such as study of the elastic properties of a single nucleus; fusion, fission, and dysfunction of mitochondrion; [ 52 ] and autophagosome–lysosome fusion. [ 53 ] As a conclusion, this study constitutes a potentially important experimental tool for single‐cell analysis and manipulation.…”
Section: Resultsmentioning
confidence: 89%
“…[ 51 ] Moreover, the trapping and transport of organelles on the particle provide a new ex vivo platform for organelle manipulation and analysis, such as study of the elastic properties of a single nucleus; fusion, fission, and dysfunction of mitochondrion; [ 52 ] and autophagosome–lysosome fusion. [ 53 ] As a conclusion, this study constitutes a potentially important experimental tool for single‐cell analysis and manipulation.…”
Section: Resultsmentioning
confidence: 89%
“…DMC did not appear to impact clearance of α‐synuclein. Although some autophagic processes can be recapitulated in cell‐free systems, [31] the complete autophagic process may not be functioning sufficiently to degrade α‐synuclein. We also investigated the levels of G6PDH enzyme as a control protein and found that G6PDH was not appreciably affected by UA treatment (Supporting Information Figure S10).…”
Section: Resultsmentioning
confidence: 99%
“… The protein machinery involved in autophagy.It consists mainly of ATG proteins. The details about the molecular players involved in autophagy are discussed elsewhere (Chinchwadkar et al, 2017; Moparthi & Wollert, 2018). Briefly, during the autophagy process in yeast, the Atg1 complex (Atg1‐Atg13‐Atg17‐Atg31‐Atg29) forms the initiation complex and leads to the pre‐autophagosomal structure (PAS) formation near the vacuole, where the autophagosomes emerge (Figure 1a) (Kamada et al, 2010).…”
Section: The Machinery Of Autophagy and Sporulationmentioning
confidence: 99%